Associations between Psychopathic Traits and Readiness for Change: An exploratory analysis. (15th April 2019) - Salcido, Christine Galvan; Ray, James V.; Caudy, Michael; Viglione, Jill; Walter, Rebecca J.
Abstract: Readiness to change (RTC) indicates an individual's recognition of a problem as well as confidence in their ability to change (Gaume, Bertholet, & Daeppen, 2016), and is hypothesized to play an important role in therapeutic processes aimed at changing offending behaviors (Polaschek & Ross, 2010). However, prior research has generally failed to consider RTC among severe offender subgroups (Hodge & Renwick, 2002 ; Howells & Day, 2007) such as those with psychopathic personality features whom have often been characterized as resistant to treatment (Harris & Rice, 2006; Salekin, 2002). In the current sample of formerly incarcerated persons (N = 70), we explore the relationship between psychopathic personality traits, as measured by the Triarchic Psychopathy Measure (TriPM; Patrick, 2010), and the unique components of RTC, as measured by an originally constructed assessment called the Change Readiness Scale (CRS). Each item of the CRS has been empirically supported and combined to form five subscales of change readiness (recognition, action, social bonds, human agency, and self-efficacy). Results show unique associations between the subscales of the TriPM and aspects of the RTC construct, yielding it necessary to further explore these relationships to better understand how these factors may contribute to treatment and justice system outcomes.